Integration practices for generating alternatives in portfolio management of new product projects - Sannino, Fabiano (2021)
The purpose of this study in portfolio management is to identify and understand the practices of integration among development projects and their interaction with the operation. The main point is that project's restructuring allows the generation of project alternatives that promote synergy and increase portfolio value. It is a cross-sectional qualitative study of selected Brazilian companies. Eight semi-structured interviews were conducted with key professionals from these companies applying content and discourse analysis to the responses. The cases reveal different integration practices among projects chosen to fit each company's operations, product scope, customer and market interaction, and management models. Research data shows that the flexibility in the product development process and operations enabled more effective changes in the original design, providing new alternatives for the portfolio process. This study highlights the existence of two types of practices that support the generation of projects' alternatives: (i) organisational practices, such as informal manager meetings, client participation in the product design and validation, centralisation of the product decision, formal meetings focused on project interfaces; and (ii) technical practices such as visual and participative methods for product definition and validation, demonstrative or demo product development, presentations of product use cases to those affected, diagrams of infrastructure and competing systems and use of a flexible production line. Although the reports indicate that these practices support better alternatives, more studies are needed to investigate these findings better.